A mediação docente no desenvolvimento da compreensão e interpretação leitora - Silva Junior, Gilberto Henrique da (2019)
This paper deals with the matter of news and report text genres teaching to High School students in the interaction perspective which is established between the text, author and reader. The general objects of the research are: to disseminate theoretical studies about reading as a mean of interaction and to emphasize the importance of the pedagogical mediation in critical readers training who are capable of understand and interpret various text genres which are presented in social life. The specific objects are: 1- To show the main strategies used by readers to comprehend and interpret news and reports; 2- To comprehend the relevance of pedagogical mediation in reading teaching; 3- To analyze news text genres reading activities proposed by textbooks, in order to identify which strategies are used by the reader to answer text comprehension and interpretation questions; 4- To propose mediate report genre reading activities, considering the necessity to motivate the reading of more complex texts throughout the school years. To achieve these purposes, it is emphasized that reading activities must be done in the interaction perspective that is establish between text-author-reader. The theoretical foundation is based mainly on the studies of Solé (1998), Kleiman (2004), Marcuschi (2008), Koch and Elias (2014); Koch (2015), Van Dijk (2017) which comprehend reading as a sociointeracional activity. The research was developed based on the following inquiry: 1- What is the school’s role in critical readers training process?; 2- How can reading strategies further text comprehension and interpretation?; 3- Which elements make reading activities more significant to students?; 4- What is the importance of pedagogical mediation in reading production activities? In corpus, news reading activities from first year of High School textbook are analyzed and, at last, a didactic sequence destined to journalistic reports text genre teaching is presented, given the necessity to amplify the complexity of text genres proposed to students. The obtained results demonstrate the textbook author’s preoccupation in doing a previous knowledge survey to students before presenting the text genre to be studied in the unit. It is also observed that the elaborated questions to the text interpretation and comprehension activities allow the elaboration of inferences by implicit relations and texts, as explicit information location. Lastly, the elements that may make reading activities more significant to High School students are understood